The Senate of the Fifth French Republic - Smith, P. author. aut Link
XIV, 225 p.
Keywords: Paul Smith examines how the Senate has attempted, since 1958, to locate itself within the French (semi-) presidential system, how it asserts its place in relation to the President, Government and National Assembly and how it has sought, in recent years, to develop an autonomous and particular sense of identity.